Susceptibility of lung epithelium to neutrophil elastase: protection by native inhibitors - L. Bingle; R. J. Richards; B. Fox; L. Masek; A. Guz; T. D. Tetley (Mediators of Inflammation)
The development of emphysema is thought to be due to an imbalance of proteases (especially neutrophil elastase [NE]) and antiproteases with loosening of the respiratory epithelium as an early event. We investigated the effect of NE on respiratory epithelial cell adherence in vitro , in the presence of varying concentrations and combinations of native inhibitors, α-1-proteinase inhibitor (PI) and secretory leukoprotease inhibitor (SLPI). SLPI was two to 12 times more effective than PI at preventing the effects of NE, especially when enzyme:inhibitor ratios were almost equivalent. Even when the concentration of SLPI was only 10% of the total (as in normal peripheral lung secretions), it gave greater protection than PI alone. This suggests that SLPI plays an important role in controlling neutrophil elastaseinduced inflammation and tissue damage.